Council on Staff Affairs (COSA), Minutes, July-August, 2018 and Agendas, August-September 2018 - Council on Staff Affairs, Valdosta State University (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 2018)
Council on Staff Affairs (COSA), Minutes, July-August, 2018 and Agendas, August-September 2018.
4 electronic documents. Council on Staff Affairs (COSA), Minutes, July 17, 2018. 6 pages. Council on Staff Affairs (COSA), Agenda, August 21, 2018. 2 pages. Council on Staff Affairs (COSA), Minutes, August 21, 2018. 6 pages. Council on Staff Affairs (COSA), Agenda, September 18, 2018. 2 pages.
Keywords: Minutes (Records); Council on Staff Affairs (Valdosta State University); Valdosta State University; Committees